P238 Role of naturally-acquired IgG in protection from S. pneumoniae lung infection. (14th November 2013) - Wilson, RJ; Jose, RJ; Barabas, M; Marshall, H; Cohen, JM; Sapey, E; Baxendale, H; Brown, JS
Abstract : Preventing Streptococcus pneumoniae lung infections will have substantial health benefits, yet existing polysaccharide vaccines are not effective against pneumonia. Identifying the mechanisms of naturally-acquired immunity to S. pneumoniae lung infections could indicate alternative preventative strategies. Human intravenous immunoglobulin (IVIG) preparations pooled from >1000 donors prevent respiratory infections in patients with hypogammaglobuniaemia. IVIG therefore provides a tool to investigate the naturally-acquired antibody responses to S. pneumoniae within a population. We have used mouse models and in vitro assays to assess the efficacy of IVIG for preventing S. pneumoniae lung infections and to identify the immunodominant target antigens. In a mouse pneumonia model, IVIG treatment was highly protective against bacteraemia (17% septicaemia v. 100% in controls, P = 0.015) and partially protected against lung infection (lung CFU log10 3.7 for IVIG v. 6.3 for controls, P = 0.041) but not against nasopharyngeal colonisation. Depletion of phagocyte subsets demonstrated that IVIG-mediated protection required neutrophils and macrophages for lungs and blood respectively. Flow-cytometry assays demonstrated that IgG within IVIG preparations opsonised S. pneumoniae effectively. Importantly, IgG opsonisation was reduced by pre-treatment of bacteria with pronase to remove bacterial surface proteins but not by depletion of anti-capsular antibody. Furthermore, in vitro assays demonstrated that IVIG facilitated phagocytosis, growth impairment and bacterial agglutination of capsule-deficient S. pneumoniae mutants, in mice IVIG depleted of anti-capsular antibody remained protective against lung infection and septicaemia. These results demonstrate that surface proteins rather than the capsule are targets for naturally-acquired adaptive immunity to S. pneumoniae . The potential S. pneumoniae protein antigen targets in IVIG were assessed using a semi-quantitative assay against 18 recombinant pneumococcal proteins. The results demonstrated significant IgG responses to the conserved pneumococcal protein antigens PhtD, PspC, PspA and PsaA. Interestingly, antibody titres to some of these antigens were reduced in sera from elderly compared to younger subjects, potentially identifying people at higher risk of S. pneumoniae infection. Our data demonstrate that the accepted paradigm that naturally-acquired immunity to S. pneumoniae depends on anti-capsular antigen is inaccurate, and instead antibody to proteins is dominant. These data will allow better evaluation of those at risk of S. pneumoniae infection and improved vaccine design.